Landscape-level changes to large mammal space use in response to a pastoralist incursion. (February 2021) - Masiaine, Symon; Pilfold, Nicholas; Moll, Remington J.; O'connor, David; Larpei, Lexson; Stacy-Dawes, Jenna; Ruppert, Kirstie; Glikman, Jenny A.; Roloff, Gary; Montgomery, Robert A.
Highlights: Pastoralist livestock and wildlife regularly compete over rangeland access around the world. In 2017, 40, 000 livestock were illegally grazed on Loisaba Conservancy, Kenya for a period of three months. The space use of seven resident species of large mammals were substantially changed via this incursion. Unregulated livestock incursions can present major disturbance events for wildlife. Interventions designed to conserve wildlife and preserve pastoralist well-being are offered. Abstract: Pastoralists and their livestock have long competed with wildlife over access to grazing on shared rangelands. In the dynamic 21st century however, the configuration and quality of these rangelands is changing rapidly. Climate change processes, human range expansion, and the fragmentation and degradation of rangeland habitat have increased competition between pastoralist livestock and wildlife. Interactions of this type are particularly apparent in East Africa, and perhaps most obvious in northern Kenya. In 2017, following months of intense drought, a pastoralist incursion of a protected area (Loisaba Conservancy) occurred in Laikipia County, Kenya. An estimated 40, 000 livestock were herded onto the conservancy by armed pastoralists where the cattle were grazed for approximately three months. Using 53 camera trap sites across the 226 km 2 conservancy, we quantified spatial patterns in site visitation rates (via spatially-explicit, temporally-dynamic Bayesian models) for seven species of large mammalian herbivores in the three-month period directly before, during, and after the incursion. We detected significant changes in space use of all large mammalian herbivores during the incursion. Furthermore, these patterns did not return to their pre-incursion state in the three-month period after the pastoralists and their livestock left the conservancy. Thus, in addition to reduced site vitiation rates for these large mammalian herbivores, we also detected considerable displacement in response to the livestock incursion. Our results illustrate that pastoralist incursions can cause large-scale disruptions of wildlife space use, supporting the notion that livestock can competitively exclude large mammalian herbivores from grazing access. We discuss the implications of this research for applied management decisions designed to alleviate competition among wildlife and pastoralist livestock for the benefit of wildlife conservation and pastoralist well-being.